The monitoring of B lymphocytes in non-lymphoma patients following rituximab treatment - Dong, Linjie; Yan, Lin; Li, Yi; Li, Mei; Feng, Weihua; Li, Xiaoqiong; Yue, Jiaxi; Zhang, Erdi; Luo, Yao; Bai, Yangjuan (Frontiers in Immunology, 2024)
RTX was initially used for non-Hodgkin’s lymphoma treatment and has been used in the clinical treatment of various autoimmune diseases as well as in antirejection and immune induction therapy for kidney transplant recipients. Following RTX treatment, the time for B cell regeneration varies among patients, but there is no unified recommendation for the frequency of B cell monitoring. This study aimed to investigate the clinical significance of periodic monitoring of peripheral blood B lymphocytes in individualized immunotherapy following rituximab (RTX) treatment in patients with different diseases. This study included 488 patients with different diseases divided in four groups who were hospitalized and followed up from April 2017 to March 2024 (including 77, 161, 120, and 130 cases of neuromyelitis optica, pemphigus, membranous nephropathy, and kidney transplant recipients, respectively). Dynamic changes in percentage and absolute count of peripheral blood B lymphocytes before and after RTX treatment were investigated in the four groups, as well as the number of B cell subsets in 32 patients with optic neuromyelitis after RTX treatment. Although most patients showed high expression of B cells after 24 weeks, less than 6.8% of patients still began to experience B cell regeneration within 4 weeks. Thus, regular B cell monitoring following RTX treatment is helpful to better track the remission and recurrence of the disease and provide effective laboratory support for the selection and implementation of individualized immunotherapy.